Tacrolimus CYP3A Single-Nucleotide Polymorphisms and Preformed T- and B-Cell Alloimmune Memory Improve Current Pretransplant Rejection-Risk Stratification in Kidney Transplantation - Crespo, Elena; Vidal-Alabró, Anna; Jouve, Thomas; Fontova, Pere; Stein, Maik; Mocka, Sonila; Meneghini, Maria; Sefrin, Anett; Hruba, Petra; Gomà, Montserrat; Torija, Alba; Donadeu, Laura; et al. (Frontiers in Immunology, 2022)
Achieving fast immunosuppression blood exposure after kidney transplantation is key to abrogate both preformed and de novo anti-donor humoral and cellular alloresponses. However, while tacrolimus (TAC) is the cornerstone immunosuppressant inhibiting adaptive alloimmunity, its blood exposure is directly impacted by different single nucleotide polymorphisms (SNPs) in CYP3A TAC-metabolizing enzymes. Here, we investigated how functional TAC-CYP3A genetic variants (CYP3A4*22/CYP3A5*3) influence main baseline clinical and immunological risk factors of biopsy-proven acute rejection (BPAR) by means of preformed donor-specific antibodies (DSA) and donor-specific alloreactive T cells (DST) in a large European cohort of 447 kidney transplants receiving TAC-based immunosuppression. 70(15.7%) patients developed BPAR. Preformed DSA and DST was observed in 12(2.7%) and 227(50.8%) patients, respectively. According to the different CYP3A4*22 and CYP3A5*3 functional allele variants, we found 4 differential new clusters impacting on fasting TAC exposure after transplantation; 7(1.6%) were classified as high metabolizers 1 (HM1), 71(15.9%) as HM2, 324(72.5%) intermediate (IM) and 45(10.1%) as poor metabolizers (PM1). HM1/2 showed significantly lower TAC trough levels and higher dose requirements than IM and PM (p<0.001) and more frequently showed TAC under-exposure (<5ng/ml). Multivariate Cox regression analyses revealed that CYP3A HM1 and IM pharmacogenetic phenotypes (HR 12.566 CI95% 1.99-79.36, p=0.007 and HR 4.532 CI95% 1.10-18.60, p=0.036, respectively), preformed DST (HR 3.482 CI95% 1.99-6.08, p<0.001), DSA (HR 4.421 CI95% 1.63-11.98, p=0.003) and DGF (HR 2.023 CI95% 1.22-3.36, p=0.006), independently predicted BPAR. Notably, a significant interaction between T-cell depletion and TAC under-exposure was observed, showing a reduction of the BPAR risk (HR 0.264 CI95% 0.08-0.92, p=0.037). Such variables but DSA, displayed a higher predictive risk for the development of TCMR. Refinement of pretransplant monitoring by incorporating TAC CYP3A SNPs with preformed DSA as well as DST may improve current rejection-risk stratification and help induction treatment decision-making.